A review on polymer nanocomposite hydrogel preparation, characterization, and applications - Azady, Md. Arif Roman; Ahmed, Sony; Islam, Md. Shafiul (European Journal of Chemistry, 2021)
Nanocomposite hydrogels, made by incorporating nanoparticles into a hydrogel matrix, have been developed to fulfill the need for materials with enhanced and predictable mechanical properties and functionality. This review breaks down the process of preparing and characterizing nanocomposite hydrogels and looks at the various applications they can be used for. Through careful selection of the nanoparticle and hydrogel types, as well as the preparation method, the degree of crosslinking and the strength of the intermolecular interactions between the nanoparticles and the hydrogel matrix can be controlled. Once the nanomaterial is prepared, the morphology, gel content, thermal stability, and mechanical properties are investigated. By varying the concentrations of nanoparticles within the hydrogel matrix, nanocomposite hydrogels with optimal functionality and mechanical properties are produced. The optimized nanomaterial can then be used for its intended application(s); here the focus is on applications in the biomedical and dye adsorption fields. With further research, it is predicted that nanocomposite hydrogels will fulfill their potential to be used in practical, everyday applications.